The (dis) symmetrization in initial literacy and its possible association with linguistic and cognitive variables (Research, Society and Development, 2021)
This study collaborates in the description of mirroring, through the assessment of students in the last year of early childhood education and literacy classes, aiming at: a) drawing a parameter of incidence of mirroring evidence in these series, b) relating mirroring in recognition and production writing of graphic symbols and, c) evaluating possible associations of mirroring with linguistic or cognitive variables. It was hypothesized that individuals are not born naturally prepared to relate sound value and a given direction of linguistic elements. The variables were: laterality, manual preference, production of symbols, punctuation marks, letters, numbers, phrases, words and writing of the name itself. The recognition of letters, not letters, symbols of other writing systems, letters in other directions and mirrored letters, reading, writing and intelligence skills were evaluated. Production and recognition were assessed with adapted and elaborated tasks. 129 students from 4 to 12 years old, of both sexes, from day care, public and private schools in the interior of Bahia participated in the research. The results showed that schoolchildren who already decode have less mirrored production and, in contrast, subjects who are not readers yet have significant evidence of mirroring in production and recognition. Mirroring occurs in the visual processing of any graphic symbols; it does not occur only with elements of the written system and can remain in students who already read. In production tasks, the higher the level of schooling, the lower the signs of mirroring. In the comparison between linguistic segments, there were signs of mirroring in letters and words, but they were not observed in sentences.